1997
DOI: 10.1016/s0954-6111(97)90009-3
|View full text |Cite
|
Sign up to set email alerts
|

Flow early in the inspiratory manoeuvre affects the aerosol particle size distribution from a Turbuhaler

Abstract: Several in vitro and in vivo studies have emphasized the importance of generating a high inspiratory flow when using a dry powder inhaler. Little attention has been paid to the influence of the inspiratory flow profile on the particle size distribution contained in aerosols generated by these devices. The internal volume of a device such as the Turbuhaler is small compared with a vital capacity breath and it is possible that all the powder has been drawn from the device before peak inspiratory flow has been ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 9 publications
2
70
2
1
Order By: Relevance
“…It has been shown that de-agglomeration of particles takes place inside the device before the metered dose leaves the DPI and is increased if the acceleration is fast at the start of inhalation [65]. Thus, the FPD will be greater and the MMAD smaller when the initial acceleration rate of the inhalation flow is fast [65,66]. Hence patients should be instructed to inhale forcefully from the beginning of their inhalation.…”
Section: Dry Powder Inhalersmentioning
confidence: 99%
“…It has been shown that de-agglomeration of particles takes place inside the device before the metered dose leaves the DPI and is increased if the acceleration is fast at the start of inhalation [65]. Thus, the FPD will be greater and the MMAD smaller when the initial acceleration rate of the inhalation flow is fast [65,66]. Hence patients should be instructed to inhale forcefully from the beginning of their inhalation.…”
Section: Dry Powder Inhalersmentioning
confidence: 99%
“…The acceleration of the flow, like the pressure change, has been shown to be critical for deaggregation of the formulation in a DPI, (14,15) because the dose is emitted in the first part of an inhalation. Overall, when the PIF was fast, then the acceleration rates were steeper than when the PIF was slow.…”
Section: Dry Powder Inhaler Inhalation Maneuversmentioning
confidence: 99%
“…(5) Hence, more attention needs to be directed to the minimum acceptable PIF achieved through each DPI rather than to the optimal flow. Also, it has been suggested that the pressure changes that occur inside the inhalation channel of each DPI (13) and the initial acceleration rate of the inhalation maneuver (14,15) are more important than PIF in the generation of the fine particle dose. Similarly, inhaled volume is also considered an important parameter of the inhalation profile and can govern the quality of the emitted dose, (15) particularly in a capsule formulation (10,16) because of the need to empty the capsule.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, both the speed and the acceleration of the inspiratory manouevre when using a DPI critically affect the respirable dose. 8,16 Although the In-CheckDial does not measure the speed of inhalation, Broeders and colleagues have shown that it correlates with PIF when patients use DPIs.…”
Section: In-checkdialmentioning
confidence: 99%